Precision Synthesis of Poly(Ionic Liquid)‐Based Block Copolymers by Cobalt‐Mediated Radical Polymerization and Preliminary Study of Their Self‐Assembling Properties. Issue 4 (13th December 2013) - Coupillaud, Paul; Fèvre, Maréva; Wirotius, Anne‐Laure; Aissou, Karim; Fleury, Guillaume; Debuigne, Antoine; Detrembleur, Christophe; Mecerreyes, David; Vignolle, Joan; Taton, Daniel; Lutz, J.‐F.; Sumerlin, B.; et al.
<x xml:space="preserve">Abstract</x> A poly(ionic liquid)‐based block copolymer (PIL BCP), namely, poly(vinyl acetate)‐b‐poly(N‐vinyl‐3‐butylimidazolium bromide), PVAc‐b‐PVBuImBr, is synthesized by sequential cobalt‐mediated radical polymerization (CMRP). A PVAc precursor is first prepared at 30 °C in bulk by CMRP of VAc, using bis(acetylacetonato)cobalt(II), Co(acac)2, and a radical source (V‐70). Growth of PVBuImBr from PVAc‐Co(acac)2 is accomplished by CMRP in DMF/MeOH (2:1, v/v). This PIL BCP self‐assembles in the sub‐micron size range into aggregated core–shell micelles in THF, whereas polymeric vesicles are observed in water, as evidenced by dynamic light scattering (DLS) and transmission electron microscopy (TEM). Thin‐solid sample cut from raw materials analyzed by TEM shows an ordered lamellar organization by temperature‐dependent synchrotron small‐angle X‐ray scattering (SAXS). Anion exchange can be accomplished to achieve the corresponding PIL BCP with bis(trifluorosulfonyl)imide (Tf2N−) anions, which also gives rise to an ordered lamellar phase in bulk samples. A complete suppression of SAXS second‐order reflection suggests that this compound has a symmetric volume fraction (f ≈ 0.5). SAXS characterization of both di‐ and triblock PIL BCP analogues previously reported also shows a lamellar phase of very similar behavior, with only an increase of the period by about 8% at 60 °C. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>